Stable-to-dynamic expansion of fault slipping area through fluid injection observed in laboratory experiments using a sub-meter scale specimen - Takatoshi Ito; Koji Aoki; Yusuke Mukuhira; Yasuo Yabe (Earth, Planets and Space)
Abstract In the field, locally applied fluid pressure can initiate fault slip, which may expand unstably over a wide area under certain conditions, generating elastic waves and inducing earthquakes. Therefore, examining the unstable expansion of the initial slip is important. However, reproducing this process in laboratory experiments, such as triaxial loading tests on small cylindrical specimens with inclined faults, is challenging. To achieve this, we prepared a sub-meter-scale cubic specimen, which was separated into two triangular prisms by a model fault. The specimen was subjected to biaxial compression of different magnitudes. A 2D array of strain gauges was embedded beneath the fault plane to measure the changes in shear strain with fault slip driven by fluid injection. Based on the experimental results, we discussed the features of the injection-induced fault slips that lead to earthquakes. The strain increased locally around the edge of the fault slipping area by approximately 10 με, which is equivalent to a shear stress of ~ 0.1 MPa. The fault slipping area first expanded gradually and then unstably beyond the fluid invasion area approximately 3 s after the slip was initiated. The unstable expansion of initial slips was suppressed by reducing the initial shear stress on the fault by 0.3 MPa. In this case, the initial shear stress was possibly too small for additional stress to accumulate at the edge of the fault-slipping area to overcome the static frictional strength of the fault. Our experimental study explicitly confirms that injection-induced aseismic slip can outpace the fluid migration front, finally leading up to a runaway rupture. It also confirms that the level of initial shear stress is important in controlling the rupture size under fluid injection. Graphical Abstract